An Insight into Giant Cell Arteritis Pathogenesis: Evidence for Oxidative Stress and SIRT1 Downregulation - Alessandro Ianni; Poonam Kumari; Shahriar Tarighi; Flavia Rita Argento; Eleonora Fini; Giacomo Emmi; Alessandra Bettiol; Thomas Braun; Domenico Prisco; Claudia Fiorillo; Matteo Becatti (MDPI AG, 2021)
Giant cell arteritis (GCA), medium and large vessel granulomatous vasculitis affecting the elderly, is characterized by a multitude of vascular complications, including venous thrombosis, myocardial infraction and stroke. The formation of granulomatous infiltrates and the enhanced accumulation of proinflammatory cytokines are typical features of this condition. The GCA pathogenesis remains largely unknown, but recent studies have suggested the involvement of oxidative stress, mainly sustained by an enhanced reactive oxygen species (ROS) production by immature neutrophils. On this basis, in the present study, we intended to evaluate, in GCA patients, the presence of systemic oxidative stress and possible alterations in the expression level of nuclear sirtuins, enzymes involved in the inhibition of inflammation and oxidative stress. Thirty GCA patients were included in the study and compared to 30 healthy controls in terms of leukocyte ROS production, oxidative stress and SIRT1 expression. Our results clearly indicated a significant increase (p < 0.05) both in the ROS levels in the leukocyte fractions and plasma oxidative stress markers (lipid peroxidation and total antioxidant capacity) in the GCA patients compared to the healthy controls. In PBMCs from the GCA patients, a significant decrease in SIRT1 expression (p < 0.05) but not in SIRT6 and SIRT7 expression was found. Taken together, our preliminary findings indicate that, in GCA patients, plasma oxidative stress is paralleled by a reduced SIRT1 expression in PBMC. Further studies are needed to highlight if and how these alterations contribute to GCA pathogenesis.